Testemunhas de Jeová: a inserção de suas crenças no texto da tradução do Novo Mundo das Escrituras Sagradas - Silva, Esequias Soares da (2007)
This study deals with the transfer of the Watchtower Society s theology that of the Jehovah s Witnesses movement, to within the text of their official version, the New World Translation of the Holy Scriptures. It describes the historical and theological contexts of the five periods that preceded the system now in force, and its brings up the main beliefs and practices ever since it was founded in 1872, in the United States, claiming the status of the only true religion on Earth. This explains the movement s scorn for the Bible translations produced by the main branches of Christianity, which it considers to be false, and that is why it decided to produce its own version. This study analizes the movement s arguments in favour of producing a Bible translation, its origin, the academical qualification of its translators, and the insertion of its beliefs and pratices into the sacred text. This study checks the Bible texts in which the movement s concepts of God: the Divine Name, Jesus Christ, and the Holy Spirit; of the hell of fire, of man s destiny, of Christ s Second Coming, and of the Cross of Christ developed during the movement s history, which were modified and transferred into the sacred text. The study concludes with a definition of the Jehovah s Witnesses religion as a human organization, with its own distinctive theological caracteristics, whose standard text is as distinctive as its theology, and which is used as a literary tool to give its doctrine a biblical mask.